A Review on Evaluation of Digital Image Watermarking Techniques (International Journal of Engineering and Computer Science, 2014)
An efficient strategy that solves many problems within a digitization is Watermarking. By embedding Intellectual Property data like the creator, licence model, creation date or another copyright information within the digital object, the digitiser can reveal they are the creator and spread this information with each copy, even when the digital object has been uploaded to a third party site. This can also be utilized to decide if a required work has been tampered with or copied. This paper describes methods to establish if an application need watermarking strategies and criteria for selecting for the most suitable type. This paper concentrates on evaluating the responsibility of the SVD, DCT and DWT dependent image watermarking for protected transmission